2020
DOI: 10.1007/s11481-020-09909-8
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s and Parkinson’s Disease-Associated LRRK2 Mutations Alter Type II Interferon Responses in Human CD14+ Blood Monocytes Ex Vivo

Abstract: The Leucine Rich Repeat Kinase 2 (LRRK2) is one of causative genes of familial Parkinson’s disease (PD). The M2397T polymorphism in LRRK2 is genetically associated with sporadic Crohn’s disease (CD). LRRK2 is expressed in human CD14+ monocytes, induced by interferon-γ (IFN-γ) and suppresses inflammatory activation. We hypothesize that IFN-γ-induced LRRK2 and inflammatory gene expression is altered by LRRK2 genetic polymorphism found in CD and PD cases. A total of 46 CD and 51 control cases, and 16 PD cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…LRRK2 mRNA is upregulated in inflamed CD intestinal tissue relative to uninflamed tissue from the same patient, and this LRRK2 expression was localized to macrophages, B cells, and dendritic cells in the lamina propria, a thin layer of connective tissue that lines the intestinal tract 72 . A recent study identified that CD14+ monocytes from the blood of CD patients with the LRRK2 M2397T variant exhibit an elevated pro-inflammatory response to IFNγ relative to healthy controls 75 . Paneth cells are specialized secretory cells in the small intestine that regulate intestinal microbiome and innate immune response.…”
Section: Lrrk2 In Pd and CD Immune Cellsmentioning
confidence: 99%
“…LRRK2 mRNA is upregulated in inflamed CD intestinal tissue relative to uninflamed tissue from the same patient, and this LRRK2 expression was localized to macrophages, B cells, and dendritic cells in the lamina propria, a thin layer of connective tissue that lines the intestinal tract 72 . A recent study identified that CD14+ monocytes from the blood of CD patients with the LRRK2 M2397T variant exhibit an elevated pro-inflammatory response to IFNγ relative to healthy controls 75 . Paneth cells are specialized secretory cells in the small intestine that regulate intestinal microbiome and innate immune response.…”
Section: Lrrk2 In Pd and CD Immune Cellsmentioning
confidence: 99%
“…LRRK2 is increased in patients with CD and the increase is possibly induced by interferon-γ (IFN-γ). A recent study has shown an elevated pro-inflammatory response of CD14+ monocytes from CD patients with the LRRK2 M2397 to IFN-γ [ 75 ]. Vice versa, transgenic mice overexpressing LRRK2 have been found exhibited more severe dextran sodium sulfate (DSS)-induced colitis than control animals [ 76 ].…”
Section: Intestinal Dysfunctions In Pdmentioning
confidence: 99%
“…By understanding how mitochondrion-triggered innate immune responses influence tuberculosis disease severity, we might one day develop hostdirected therapeutics designed to correct imbalances in these responses and promote positive tuberculosis patient outcomes. Likewise, because mitochondrial mutations that confer susceptibility to mycobacterial infection are also associated with several chronic diseases, including Parkinson's disease (PD) (12)(13)(14)(15), Crohn's disease (16)(17)(18)(19), inflammatory bowel disease (20)(21)(22), and cancer, understanding how they alter mitochondrial function and dysregulate immune responses will help illuminate common molecular mechanisms driving these otherwise disparate diseases.…”
mentioning
confidence: 99%